High resolution structure of ribosomal subunits RNA/RNA and protein/RNA interactions - Ban, Nenad (Henry Stewart Talks, 2008)
X-ray crystallography, Protein synthesis, High resolution structure of ribosomal subunits, RNA motifs and interactions, RNA protein interactions, Metal ions stabilizing RNA structure, Functional implications of RNA/RNA and RNA/protein interactions during protein synthesis